WACANA DAN PRAKTIK ETIKA AKUNTAN PUBLIK DALAM STRUKTURASI (+SQ) - Unti Ludigdo (EKUITAS (Jurnal Ekonomi dan Keuangan), 2009)
This research aims to understand the ethical discourse and practice of the professional accountants in a public accounting office (KAP) area. Hence, it is developed with the basis of interpretive paradigm. To explore the comprehensive meaning of ethics in everyday practice, writer used a collaborative theory (ethno methodology, structural and spiritual intelligence or SQ). This research shows two indications. First, in the KAP’s management is more informal climate and the managing partner has a strong strength change  in the organization. In the framework of ESQ, it can be understood that the informal pattern developed was the manifestation of the chief’s internal dimension which are not always based on a certain convention, a flexible behavior, a tendency to maintain life quality inspired by visions and values, self  tendency to see the relationship between lots of things (to view in a “holistic” way). Second, the structural pattern is not only rolling in the context of interaction between human being and organization, but also in the context of social environment setting.  With an informal pattern developed in a KAP, the discourse and practical of ethics which is developed here is coming from the  chief’s effort  and  shared of value personally.  While, this effort is inseparable  from the social context coped with this individual and organizational context.  Especially, ethical practice  is always happened because the existence of a strong external pressure from multiparty.